Framing sport managers’ profile: A systematic review of the literature between 2000 and 2019 - Santos, José Miguel; Batista, Paula; Carvalho, Maria José (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The present study is a systematic review focused in sport managers’ profile and the main purpose is to map the literature of sport managers’ competencies and tasks from January of 2000 to January of 2019. The search was made on EBSCO, B-on, Web Science and Scopus using the following keywords: ‘sport managers OR sport directors OR sport administrators’, ‘sport managers AND qualifications’, ‘sport managers AND responsibilities’, ‘sport managers AND traits’, ‘sport managers AND roles’, ‘sport managers AND competencies’ and ‘sport managers AND characteristics’ in peer reviewed articles and dissertations. After applying the inclusion criteria, 65 studies were selected. Sport managers are, predominantly, men in their thirties and forties, with a degree in physical education. A sport manager must have competencies such as leadership, integrity, specific knowledge, resource allocation, authority’s delegation, employees’ motivation and innovative thinking to accomplish the most important and more time consuming responsibilities like planning/organization, coordination/evaluation or information.